2013
DOI: 10.1002/jgra.50567
|View full text |Cite
|
Sign up to set email alerts
|

Earth's collision with a solar filament on 21 January 2005: Overview

Abstract: , one of the fastest interplanetary coronal mass ejections (ICME) of solar cycle 23, containing exceptionally dense plasma directly behind the sheath, hit the magnetosphere. We show from charge-state analysis that this material was a piece of the erupting solar filament and further, based on comparisons to the simulation of a fast CME, that the unusual location of the filament material was a consequence of three processes. As the ICME decelerated, the momentum of the dense filament material caused it to push t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 98 publications
(111 reference statements)
2
29
0
Order By: Relevance
“…Indeed, the helium density exceeds by 10 % the proton number density, consistent with the photospheric abundance of He 2+ . Considering the similarity of these features with those described by Burlaga et al (1998) and Kozyra et al (2013), we suggest that this high-density region at the rear of the magnetic cloud might be filament material.…”
Section: +supporting
confidence: 87%
“…Indeed, the helium density exceeds by 10 % the proton number density, consistent with the photospheric abundance of He 2+ . Considering the similarity of these features with those described by Burlaga et al (1998) and Kozyra et al (2013), we suggest that this high-density region at the rear of the magnetic cloud might be filament material.…”
Section: +supporting
confidence: 87%
“…What could this "plasma plug" be? Kozyra et al (2013) have found that high plasma density solar filaments (the most sunward part of CMEs) play prominent roles in extreme ICME events. Perhaps with more detailed research and simulations we will eventually know the answer of whether this hypothesis or another one can explain the 1859 storm in detail.…”
Section: Case History: Super Magnetic Storm Of September 1-2 1859mentioning
confidence: 99%
“…Such events remain rare compared to the observed fraction of CMEs associated with prominence eruptions. A possible example is the 21 January 2005 ICME event, where both charge state analysis and simulation (Kozyra et al 2013;Manchester et al 2014b) strongly suggest that cold dense prominence material associated with a fast CME impacted the Earth.…”
Section: Plasma Evolutionmentioning
confidence: 99%